Journalism in the labyrinth - López-García, Xosé (Anuario ThinkEPI, 2023)
Many citizens have announced the end or death of journalism; many citizens have highlighted the role of journalism in the past; many citizens have announced a great future for digital journalism. In recent years, in a context of great transformations in the communication ecosystem, we have heard it all when talking about the present and the future of journalism. The multiplication of digital native media, the emergence of "countermedia" or fake media, the hybridization of models, the emergence of new journalistic movements, the emergence of new peripheral actors- are all fueling a communication ecosystem where the boundaries of what is journalism and what is not are increasingly blurred. In any case, journalism will be what current and future societies are able to agree upon. We know what it has been and what it can be, as well as the role it can play in making democratic and pluralistic societies function better and have a good supply of information. But the future is not written; it has to be built, and journalism, which belongs to society -its owners are not only those who practice it or those who create industries around journalism- has to earn it. And, while it tries to do so, journalism is navigating the labyrinth of today´s complex network societies.
Keywords: Digital journalism; Digital society; Metaverse; Fediverse; Journalistic movements